2009
DOI: 10.1515/jpm.2009.042
|View full text |Cite
|
Sign up to set email alerts
|

Pregnant women's perception of cesarean section on demand

Abstract: Aims: To assess pregnant women's awareness of and attitudes towards cesarean section (CS) on demand, as well as to identify specific target groups by focusing on differences dependant on the participants' background, parity and intended mode of delivery. Methods: The study was conducted at two centers during three months. German-speaking pregnant women were invited to answer an anonymous, structured questionnaire. We compared urban vs. rural, nulliparous vs. parous and women opting for a CS vs. denying this wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
17
0
2

Year Published

2011
2011
2018
2018

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 23 publications
0
17
0
2
Order By: Relevance
“…General consequences of a traumatic birth experience vary from feelings of low self‐esteem to difficulty breastfeeding and problems with sexuality , to the wish for an elective cesarean section in a subsequent pregnancy and fear of childbirth . Very recently, a systematic review was published on the effect of perinatal PTSD symptoms on child outcomes .…”
Section: Introductionmentioning
confidence: 99%
“…General consequences of a traumatic birth experience vary from feelings of low self‐esteem to difficulty breastfeeding and problems with sexuality , to the wish for an elective cesarean section in a subsequent pregnancy and fear of childbirth . Very recently, a systematic review was published on the effect of perinatal PTSD symptoms on child outcomes .…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, Tschudin et al; 2009 have described specific strategies used to increase pregnant women's awareness of and attitudes towards cesarean section demand, as well as to focus in their perception of CS which based on misconceptions [15]. One of the of the Egyptian researches done at Gamal Abed Elnaser hospital, Alexandria from 1998 to 2005 reported that CS was very high and trend to increase and was significant, unfortunately this will be as an indicator to take appropriate strategies to reduce the rate of CS, patient's records lack for essential information that can give justification for CS [16].…”
Section: Discussionmentioning
confidence: 99%
“…The only study that has specifically addressed media representations of cesarean section is Brazilian; a 20‐year review of women's magazines, which concluded that most articles were balanced, not favoring cesarean section over vaginal birth, although the sources of information used were not optimal . Media approaches to cesarean section at maternal request have not been explored, but one Swiss study of women's attitudes to cesarean section on demand noted that print media reports and television were frequently cited means by which women found out that they could request a cesarean section .…”
mentioning
confidence: 99%